Knowledge, understanding, and uptake of noninvasive prenatal testing among Latina women. (21st May 2015) - Farrell, Rachel; Hawkins, Anne; Barragan, Deborah; Hudgins, Louanne; Taylor, Joanne
Abstract Objective The aim of this study is to assess Latina patient understanding of noninvasive prenatal testing (NIPT) and identify what factors influence uptake/refusal to NIPT to adapt counseling to the needs and interests of this population. Methods Mixed‐methods survey in English and Spanish administered to pregnant Latina patients throughout pregnancy. Results Sixty‐three women participated in our study (67% response rate); 34.9% chose to do NIPT, and 65.1% declined. Approximately half of participants (44%) had an NIPT knowledge score of ≤3 out of six total questions. Two of the most significant factors influencing uptake of NIPT were a higher reported educational level (p = 0.015) and a higher NIPT knowledge score (p = 0.014); 42.9% of participants knew that NIPT only screens for certain chromosomal conditions; 39% of women who declined NIPT would never consider NIPT in the future. Conclusions One‐third of Latina women elected NIPT; a higher reported educational level and language were most predictive of this choice. Overall knowledge was significantly lower for women who declined NIPT. Lower knowledge may suggest that not all women are making informed decisions because of varying degrees of informed consent. Providing culturally tailored information can help women navigate the complexities of prenatal testing in order to make decisions most aligned with their values. © 2015 John Wiley & Sons, Ltd.